Dakwah Humanis Melalui Gerakan Tarekat Tijaniyah - Fathulloh, Ziaulhaq; Ghulam, Zainil; Farid, Achmad (Institut Agama Islam Syarifuddin Lumajang, 2023)
Abstract Humanist preaching is a way of preaching that aims to inspire people to behave more humanely. Meanwhile, tariqah is a guide to practicing worship in accordance with the teachings of the Prophet followed by the companions, tabi'i, and tabi'it tabi'in. Sheikh Ahmad At-Tijany in his teaching of tarbiyah ruhiah (spiritual education) considers tarekat as a means to achieve a position as the heir of the prophets and become insanul kamilah. The purpose of this study is to analyze the process of preaching through the activities of the Tijaniyah tarekat, which is believed to have strategic value in improving the quality of Muslims. The research method used is descriptive qualitative method, by collecting data through observation, interviews, and documentation, which are then analyzed. The results showed that da'wah through tarekat is an effective approach. Da'wah through tariqah focuses more on individuals, where members of the tariqah are given attention and da'wah material that suits their needs and desires. This is evident from the changes in the attitudes and morals of the congregation who are more obedient to the teachings of Islam, including in social aspects and time management according to the teachings of Sheikh Ahmad At-Tijani, such as practicing wirid, performing worship on time, interacting well, and emphasizing akhlakul karimah and reading the Al-Quran. Abstrak Dakwah humanis adalah salah satu cara berdakwah yang bertujuan untuk menginspirasi manusia agar berperilaku lebih manusiawi. Sementara itu, tarekat merupakan suatu panduan untuk menjalankan ibadah sesuai dengan ajaran Rasulullah saw yang diikuti oleh para sahabat, tabi'i, dan tabi'it tabi'in. Syekh Ahmad At-Tijany dalam pengajarannya tentang tarbiyah ruhiah (pendidikan ruhani) menganggap tarekat sebagai sarana untuk mencapai posisi sebagai pewaris para nabi dan menjadi insanul kamilah. Tujuan penelitian ini adalah untuk menganalisis proses berdakwah melalui kegiatan tarekat Tijaniyah, yang diyakini memiliki nilai strategis dalam meningkatkan kualitas umat Islam. Metode penelitian yang digunakan adalah metode deskriptif kualitatif, dengan mengumpulkan data melalui observasi, wawancara, dan dokumentasi, yang kemudian dianalisis. Hasil penelitian menunjukkan bahwa dakwah melalui tarekat merupakan pendekatan yang efektif. Berdakwah melalui tarekat lebih berfokus pada individu, di mana anggota tarekat diberikan perhatian dan materi dakwah yang sesuai dengan kebutuhan dan keinginan mereka. Hal ini terbukti dari perubahan sikap dan akhlak jama'ah yang lebih taat terhadap ajaran Islam, termasuk dalam aspek sosial dan pengaturan waktu sesuai ajaran Syekh Ahmad At-Tijani, seperti mengamalkan wirid, menjalankan ibadah tepat waktu, berinteraksi dengan baik, serta menekankan pada akhlakul karimah dan membaca Al-Quran.